PENGARUH POLA LATIHAN LARI TERHADAP PENINGKATAN KECEPATAN LARI 60 METER PADA SISWA SD NEGERI 170/VIII PURWOHARJO KABUPATEN TEBO - Deka Ismi Mori Saputra; endri - jasman (Jurnal Muara Pendidikan, 2018)
Running 60 meters is one of the branches of athletic sports. To achieve maximum results in a 60 meter run, maximum and programmed training is needed. The running practice pattern has a significant influence to train a 60 meter running speed.The study was conducted from September to November 2011 at SDN 170 / VIII Rimbo Bujang District. Tebo with a population of all male grade V students with a total sample of 20 people. The data was collected through pre-test and post-test and the results of the data obtained were processed by T-Test testing using a statistical system and assisted with Ms. Data Processing Application program. Excel. Based on data analysis there is a significant difference between the speed of students before and after training using a running exercise pattern. For this reason, it is advisable for athletic trainers to further improve their discipline and training programs to be able to see better results.